PENGARUH KEMUDAHAN, PROMOSI, RESIKO DAN FITUR TERHADAP PENGGUNAAN FLIP DENGAN VARIABEL INTERVENING SIKAP DI BANGKALAN - Andjani, Thalia; Tarman, Manah; Dawam, Aulia (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
This study was made to determine the effect of ease of use, promotion, risk and service features on the use of e-wallet (Flip) with attitude as an intervening variable in Bangkalan City. The independent variables are ease of use, promotion, risk, and service features, with the dependent variable being use and the intervening variable being attitude. The sample is the population of Bangkalan city totaling 100 respondents. Sampling was done by Snowball sampling technique. The analysis technique used is validity test, reliability test, normality test, multiple linear regression test including f test and t test. The results showed that simultaneously the x variable had an effect on the z variable (attitude) F counted 68,413 and a significance value of 0.00 <0.1, simultaneously the x variable had an effect on the y variable (Usage) with an calculated F value of 121,605 and a significance value of 0, 00 < 0.1, the variable y affects the variable z because in equation 1 the result is a significance value of 0.058 > 0.05, but simultaneously the variable x on y through z does not have a significant effect because in equation 2 the value of direct influence > influence indirect